Analysis of compensation systems of higher education institutions employees - M. A. Borovskaya; M. A. Masych; M. R. Bechvaya (Высшее образование в России)
In modern conditions, improvement of compensation system of higher educational institutions employees becomes more and more topical problem. The article presents the comparative analysis of compensation systems of the higher school employees which allowsenables to stimulate the improvement processes of raising the education quality. A salarydynamics of higher education institutions faculty added of all financing sources is presented. Higher education institutions with the worst and the best indicators of the relation of an average monthly employees salary to an average monthly salary on region economy are given.